PARLIAMENTARY ACTIVITY OF UNDO IN LABOURS UKRAINIAN PUBLIC-POLITICAL FIGURES AND OF THAT TIME SOVIET AND POLISH RESEARCH WORKERS - Пуйда, Р. Б. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Idea, 2019)
Speech goes in the article about parliamentary activity of the Ukrainian nacional-demokratic association in labours Ukrainian public-political figures and of that time soviet and Polish research workers.